2020
DOI: 10.11648/j.abb.20200803.12
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Agro-chemicals on Beekeeping in East and West Gojjam Zones of Amhara Region, Ethiopia

Abstract: The study was conducted in West and East Gojjam Zones of Amhara Region Ethiopia to determine commonly used agro-chemicals and timing of applications, their effects on honeybee by itself and beekeeper farmers used cultural practices to minimize agro-chemical side effects on honeybee; Questionnaire survey methods, key informants interview and focus group discussion were used for the study. In the questionnaire survey, 384 respondent beekeepers from 4 Woredas, 20 Kebeles (376 male and 8 female) were interviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The result is also in line with Ayele et al. ( 2020 ), in which similar kinds of pests and predators were observed and the frequency of each type of pest and predator was similar.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result is also in line with Ayele et al. ( 2020 ), in which similar kinds of pests and predators were observed and the frequency of each type of pest and predator was similar.…”
Section: Discussionsupporting
confidence: 91%
“…The present result indicated that the incidence of amoeba disease was comparatively higher in the Fagita Lekoma district (58.9%) than (in Jawi) (51.88%). This shows that amoeba disease is more prevalent in all aspects than the other honeybee diseases, even if Nosema and amoeba diseases are more prevalent in the rainy season (Ayele et al., 2020 ). The differences in prevalence between seasons were statistically non‐significant ( χ 2 = 3.31; p = 0.091), as shown in Table 8 , but numerically, the summer season is more affected than the dry season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improper pesticide use in crop production is a source of socio-economic conflict among farmers, and poisoning of honeybees by these chemicals has increased over time, with some beekeepers losing all of their colonies as a result of agrochemical use. According to a study conducted by Bizuayehu in the east and west Gojjam Zones of the Amhara Region, on average, 1,736, 4036, and 1,890 honeybee colonies die, abscond, and dwindle each year [16]. This suggests that the application of various insecticides on crops has a significant impact on beekeepers' bottom lines.…”
Section: Constraints Of Beekeepingmentioning
confidence: 99%